Abstract 231: Rescue Stenting for Failed Mechanical Thrombectomy in Acute Ischemic Stroke:An Analysis of the SVIN Registry - Aaron C. Rodriguez‐Calienes; Diogo Haussen; Mahmoud H. Mohammaden; Raul G. Nogueira; Alhamza R. Al‐Bayati; Ameer E. Hassan; Wondwossen G. Tekle; Souhm K. Desai; Juan Vivanco‐Suarez; Milagros Galecio‐Castillo; Johanna T. Fifi; Shahram Majidi; et al. (Stroke: Vascular and Interventional Neurology)
Introduction Mechanical thrombectomy (MT) often fails to achieve successful reperfusion in up to 20% of acute ischemic stroke (AIS) patients with large vessel occlusion (LVO) [1, 2]. Rescue strategies options, including balloon angioplasty alone, rescue stenting (RS) alone, or stent with balloon angioplasty, have shown promise in observational studies and meta‐analyses [3, 4]. We aimed to evaluate the association between RS with functional outcomes compared to medical management (MM) in anterior circulation LVO‐AIS patients who underwent failed MT. Methods This retrospective cohort study utilized prospectively collected data from the Society of Vascular and Interventional Neurology (SVIN) Registry, including adult patients with AIS who experienced a failed MT at 14 comprehensive stroke centers. A failed MT was defined as a modified Thrombolysis in Cerebral Infarction (mTICI) score of 0 to 2a after multiple attempts to clot retrieval. The patients were divided into two groups: those who received RS and those who only received MM. The primary efficacy outcome was the shift in the degree of disability, as measured by the modified Rankin Scale (mRS), at 90 days. Additional outcomes included functional independence (defined as a 90‐day mRS score of 0‐2), symptomatic intracranial hemorrhage (sICH), and mortality at 90 days. These outcomes were assessed using uni‐ and multivariable logistic regression models. Results A total of 642 patients were included in the analysis. The RS group consisted of 294 (45.8%) patients, while the MM group comprised 348 (54.2%) patients. A mTICI score of 2b‐3 was achieved in 242/293 (82.6%) patients in the RS group. Compared to the MM group, the RS showed a favorable shift in the overall 90‐day mRS distribution (adjusted common odds ratio [OR]=1.97, 95% CI 1.36–2.85, p=<0.001), higher rates of functional independence (RS: 30.7% vs. MM: 12%, adjusted OR [aOR]=2.39, 95% CI 1.34‐4.26, p=0.003), lower rates of sICH (RS: 2.7% vs. MM: 9%, aOR=0.32, 95% CI 0.14‐0.71, p=0.005), and lower 90‐day mortality (RS: 29.5% vs. MM: 49.7%, aOR=0.49, 95% CI 0.33‐0.74, p=<0.001). Conclusion RS showed promising functional outcomes compared to MM. RS was associated with improved functional independence, reduced sICH rates, and lower 90‐day mortality. The RS group exhibited a favorable shift in the 90‐day mRS distribution, indicating better overall functional outcomes. These findings support RS as a potential rescue strategy for AIS patients with failed MT, with implications for clinical decision‐making. However, further prospective studies are needed to validate these observations and optimize outcomes.